RECENT MOTIVATIONAL TRENDS IN IMPROVING THE HUMAN RESOURCE MANAGEMENT OF EDUCATIONAL INSTITUTIONS: TREN MOTIVASI TERKINI DALAM PENINGKATAN MANAJEMEN SDM LEMBAGA PENDIDIKAN - Ramadan, Wildan Rizki; Rindanigsih, Ida (Antis Publisher, 2023)
Recent motivational trends in human resource management (HRM) of educational institutions and their implementation strategies. The focus on work flexibility, continuous career development, work-life balance, and employee engagement and participation are highlighted. The implementation of hybrid work models, use of technology to enhance flexibility, holistic career development programs, learning approaches that support career growth, focus on employee well-being, and implementation of work-life balance policies are explained in depth. Employee engagement mechanisms through collective decisions and the development of participation in the decision-making process are also detailed. The research method uses a library research approach to analyze current motivational trends in human resource management (HRM) of educational institutions. This research method is based on literature study and analysis of relevant documents from sources such as scientific journals, books, and related research reports. The research concludes that a holistic approach to HR management can create an adaptive, motivating and growth-oriented work environment, bringing significant benefits to employees and the educational institution as a whole.